Climate change implications of electronic waste: strategies for sustainable management - Akeeb Adepoju Fawole; Ochuko Felix Orikpete; Nwakamma Ninduwezuor Ehiobu; Daniel Raphael Ejike Ewim (Bulletin of the National Research Centre, 2023)
Abstract Background This paper addresses the escalating global issue of electronic waste (e-waste), a consequence of the burgeoning demand for electronic products coupled with their transient lifespan. The rapid accumulation of e-waste is a significant concern, especially in the context of climate change, necessitating a detailed analysis of current management strategies and the development of sustainable management practices. The intricate relationship between e-waste and climate change is emphasized, illustrating how improper disposal and recycling practices substantially contribute to greenhouse gas emissions. Main body of the abstract A meticulous analysis is conducted to critique the prevailing e-waste management strategies, identifying their shortcomings and the urgent need for enhancement and globalization of these protocols. The paper argues for a fortified, universal approach to e-waste management to address the deficiencies in current methodologies. A set of strategic, sustainable solutions for e-waste management is proposed, encompassing comprehensive regulatory frameworks, advanced recycling technologies, the incorporation of eco-design principles, and the enhancement of consumer awareness. These solutions pivot around the circular economy concept, viewing waste as a valuable resource rather than a disposal predicament, thereby promoting sustainability. Short conclusion The paper concludes that a consolidated, global approach to e-waste management is imperative for addressing the proliferation of discarded electronics and is pivotal in the wider context of mitigating climate change and fostering sustainable development. It underscores the transformative potential of sustainable e-waste management, transforming a formidable challenge into an opportunity for environmental conservation, economic growth, and societal progress, emphasizing the importance of viewing e-waste management as a vehicle for sustainability.